Analisis Tingkat Utilitas Dan Penjadwalan Produksi Mesin Digester Menggunakan Metode Indikator Pada Ptpn Iv Gunung Bayu Sumatera Utara - Pratiwi, Selli; Sutrisno, Sutrisno; Polewangi, Yudi Daeng (Mahesa Research Institute, 2024)
Production scheduling in the industrial world has an important role as a form of decision making. The company strives to have the most effective and efficient scheduling so as to increase the productivity produced by saving production completion time to a minimum. The problem is the company has not implemented a scheduling of production machines by using a certain scheduling method that suits the situation and condition of these machines. This study aims to determine the level of utility in the digester machine at PT. Perkebunan Nusantara IV PKS Gunung Bayu and scheduling work assignments on a digester machine using the indicator method can minimize production completion time. The method used is the indicator method. This method minimizes turnaround time by prioritizing machines with large capacity while still showing engine efficiency and predetermined turnaround time. The results of scheduling analysis using the indicator method produces an optimal schedule, with 14,784 hours available only 12,162 working hours of the digester machine, the difference in hours is 2,622 hours. The average utility of four digester machines is 82.26% and the average machine utility per month of the four digester machines reaches an average of 82.39%, so the average utilization of this digester machine is optimal (high).